2015
DOI: 10.1016/j.jmr.2015.02.005
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of dynamic nuclear polarization in insulating solids

Abstract: Dynamic nuclear polarization (DNP) is a technique used to enhance signal intensities in NMR experiments by transferring the high polarization of electrons to their surrounding nuclei. The past decade has witnessed a renaissance in the development of DNP, especially at high magnetic fields, and its application in several areas including biophysics, chemistry, structural biology and materials science. Recent technical and theoretical advances have expanded our understanding of established experiments: for exampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
123
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(127 citation statements)
references
References 82 publications
(99 reference statements)
4
123
0
Order By: Relevance
“…In a previous study conducted at 600 MHz (Fricke et al 2014), this system exhibited one of the best resolutions ever achieved for a protein sample under DNP conditions (Can et al 2015;Su et al 2015). Increasing the field strength to 800 MHz and using the biradical AMUPol (Sauvee et al 2013), the observed line-widths at half height are about 22 % smaller, improving the overall resolution of the spectrum sizably.…”
Section: Contentmentioning
confidence: 89%
“…In a previous study conducted at 600 MHz (Fricke et al 2014), this system exhibited one of the best resolutions ever achieved for a protein sample under DNP conditions (Can et al 2015;Su et al 2015). Increasing the field strength to 800 MHz and using the biradical AMUPol (Sauvee et al 2013), the observed line-widths at half height are about 22 % smaller, improving the overall resolution of the spectrum sizably.…”
Section: Contentmentioning
confidence: 89%
“…With the application of dynamic nuclear polarization (DNP), one could even gain further in the signal-tonoise ratio, up to a factor of 660. (Can et al 2015) Unfortunately, starting at the freezing temperature of the solvent water, one typically observes a significant broadening of the protein resonances (Linden et al 2011;Siemer et al 2012). This effect compromises most benefits of an increased signal strength.…”
Section: Introductionmentioning
confidence: 99%
“…As the magnetic field increases, the efficiency of the SE decreases rapidly as predicted by theory and also observed in experiments. 4,17,19,53 Pulsed DNP, in general, and the NOVEL experiment, in particular, do not depend on the B 0 . An analogy is that cross polarization is operating at all magnetic fields in solid state NMR.…”
Section: Discussionmentioning
confidence: 83%
“…14,[17][18][19] Single crystals were harvested and polished to fit into a quartz capillary of 0.4 mm inner diameter for experiments at 5 T. For experiments at 0.35 T, a larger sample that fit into a 4 mm EPR sample tube was used. In order to suppress the 1 H NMR signal from trapped solvent, we used perdeuterated ethanol (Cambridge Isotope).…”
Section: Experimental Samplesmentioning
confidence: 99%
See 1 more Smart Citation